Digital Marketplace Training for Strengthening Rural Capacity at Kademangan Village, Cianjur, Indonesia - Mustika Sari; Reni Dian Octaviani; Nursery Alfaridi Nasution (Jurnal IPTEK Bagi Masyarakat, 2026)
The digital transformation of MSMEs is a crucial strategy for enhancing competitiveness and business sustainability in the digital economy. This Community Service (PKM) activity aims to enhance the capacity of MSMEs in Kademangan Village, Cianjur Regency, to utilize the marketplace as a digital marketing tool. The method used was training and direct mentoring for 21 MSMEs through material delivery, practice, and interactive discussions. The results of the activity showed an increase in participants' digital literacy, particularly in creating online stores, managing products, promoting strategies, and managing orders and customer service. A post-training evaluation showed that 90% of participants felt ready to implement online businesses independently. This activity contributed to strengthening the digital capacity of village MSMEs and supporting the development of a technology-based economy.